Crigler‐Najjar Syndrome Type 1: Pathophysiology, Natural History, and Therapeutic Frontier. Issue 6 (5th February 2020) - Strauss, Kevin A.; Ahlfors, Charles E.; Soltys, Kyle; Mazareigos, George V.; Young, Millie; Bowser, Lauren E.; Fox, Michael D.; Squires, James E.; McKiernan, Patrick; Brigatti, Karlla W.; Puffenberger, Erik G.; Carson, Vincent J.; et al.
Abstract : Background and Aims: We describe the pathophysiology, treatment, and outcome of Crigler‐Najjar type 1 syndrome (CN1) in 28 UGT1A1 c.222C>A homozygotes followed for 520 aggregate patient‐years. Approach and Results: Unbound ("free") bilirubin (Bf ) was measured in patient sera to characterize the binding of unconjugated bilirubin (BT ) to albumin (A) and validate their molar concentration ratio (BT /A) as an index of neurological risk. Two custom phototherapy systems were constructed from affordable materials to provide high irradiance in the outpatient setting; light dose was titrated to keep BT /A at least 30% below intravascular BT binding capacity (i.e., BT /A = 1.0). Categorical clinical outcomes were ascertained by chart review, and a measure (Lf ) was used to quantify liver fibrosis. Unbound bilirubin had a nonlinear relationship to BT (R 2  = 0.71) and BT /A (R 2  = 0.76), and Bf as a percentage of BT correlated inversely to the bilirubin–albumin equilibrium association binding constant (R 2  = 0.69), which varied 10‐fold among individuals. In newborns with CN1, unconjugated bilirubin increased 4.3 ± 1.1 mg/dL per day. Four (14%) neonates developed kernicterus between days 14 and 45 postnatal days of life; peak BT  ≥ 30 mg/dL and BT /A ≥ 1.0 mol:mol were equally predictive of perinatal brain injury (sensitivity 100%, specificity 93.3%, positive predictive value 88.0%), and starting phototherapy after age 13 days increased this risk 3.5‐fold. Consistent phototherapy with 33‐103 µW/cm 2 nm for 9.2 ± 1.1 hours/day kept BT and BT /A within safe limits throughout childhood, but BT increased 0.46 mg/dL per year to reach dangerous concentrations by 18 years of age. Liver transplantation (n = 17) normalized BT and eliminated phototherapy dependence. Liver explants showed fibrosis ranging from mild to severe. Conclusion: Seven decades after its discovery, CN1 remains a morbid and potentially fatal disorder.